2020
DOI: 10.1007/s00217-020-03493-0
|View full text |Cite
|
Sign up to set email alerts
|

The antimycotic effect of ellagitannins from raspberry (Rubus idaeus L.) on Alternaria alternata ŁOCK 0409

Abstract: Alternaria spp. fungi, characterized by a high tolerance to unfavorable environmental conditions, are one of the threats for foods of plant origin. The increasing incidence of diseases caused by a demanding lifestyle, and a higher social awareness of the role of a diet in maintaining health and good condition, results in the dynamically growing demand for natural protective measures that would be safe for consumers. Ellagitannins, i.e. a group of bio-active polyphenols, may constitute an alternative for chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Alternaria toxins have been detected by earlier researchers in raspberry and raspberry juice, but in rather low concentrations [21,43]. The reason for that could be the ability of red raspberry to produce ellagitannins, bio-active polyphenols that inhibit the growth of Alternaria alternata [44]. Juan et al [22] also detected low levels of Alternaria mycotoxins in strawberries.…”
Section: Levels Of Mycotoxins In Berry Fruitsmentioning
confidence: 94%
“…Alternaria toxins have been detected by earlier researchers in raspberry and raspberry juice, but in rather low concentrations [21,43]. The reason for that could be the ability of red raspberry to produce ellagitannins, bio-active polyphenols that inhibit the growth of Alternaria alternata [44]. Juan et al [22] also detected low levels of Alternaria mycotoxins in strawberries.…”
Section: Levels Of Mycotoxins In Berry Fruitsmentioning
confidence: 94%
“…Using untargeted metabolomics, we found that T. quadrialata produced a diversity of ellagitannins, a class of hydrolyzable tannins that are characteristic anti-herbivore defense compounds of the plant family Melastomataceae ( Serna and Martinez, 2015 ). Ellagitannins are well-known in human medicine for their anti-inflammatory ( Gatis-Carrazzoni et al., 2019 ), anti-bacterial ( Araujo et al., 2021 ; Gontijo et al., 2019 ), anti-fungal ( Klewicka et al., 2020 ), and anti-viral ( Kesharwani et al., 2017 ) activities. In the alkaline midgut of insects, these compounds act as strong oxidants ( Barbehenn et al., 2006 ) with negative consequences for herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…Plant extracts rich in ETs show antimicrobial properties against, e.g., Escherichia coli , Salmonella enteritidis , Staphylococcus aureus , Bacillus subtilis , Klebsiella pneumoniae , Alternaria alternata , Fusarium oxysporum , and Rhizoctonia solani (Al‐Zoreky, 2009; Ascacio‐Valdés et al, 2013). These compounds have also been shown to inhibit the growth of certain viruses, fungi, and yeasts (Ascacio‐Valdés et al, 2013; Corthout et al, 1991; Klewicka et al, 2016, 2020).…”
Section: Introductionmentioning
confidence: 99%